2016
DOI: 10.4102/ajod.v5i1.202
|View full text |Cite
|
Sign up to set email alerts
|

Use of consumer wireless devices by South Africans with severe communication disability

Abstract: BackgroundAdvancements in wireless technology (e.g. cell phones and tablets) have opened new communication opportunities and environments for individuals with severe communication disabilities. The advancement of these technologies poses challenges to ensuring that these individuals enjoy equal access to this increasingly essential technology. However, a paucity of research exists.ObjectivesTo describe the nature and frequency with which South African adults with severe communication disabilities have access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Text-to-speech synthesis in various South African languages available across multiple operating systems and integrated into specific AAC applications could go a long way in giving many South Africans with severe communication disabilities ‘a voice’ (Schlünz et al 2017). The ever-increasing availability of portable and specifically mobile technology has put potential AAC solutions into the hands of many who could previously not obtain them (McNaughton & Light 2013), although physical access to these devices may require additional adaptations (Bornman et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Text-to-speech synthesis in various South African languages available across multiple operating systems and integrated into specific AAC applications could go a long way in giving many South Africans with severe communication disabilities ‘a voice’ (Schlünz et al 2017). The ever-increasing availability of portable and specifically mobile technology has put potential AAC solutions into the hands of many who could previously not obtain them (McNaughton & Light 2013), although physical access to these devices may require additional adaptations (Bornman et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of the world's population resides in low-and middle-income countries, where risk for and prevalence of disability is significantly higher [92]. High adoption rates of mobile technologies in low and middle-income regions represent an opportunity to facilitate the roll-out of mobile technology-based AAC solutions [93,94]. GS-based AAC systems that are specific and appropriate to the cultures, languages, and contexts of the populations residing in low-and middle-income countries are urgently needed [95].…”
Section: Recommendations For Further Studies and Design Projectsmentioning
confidence: 99%
“…Technology-mediated friendships (Asbjørnslett et al, 2011) were also evident in the interviews; all participants used social media such as Facebook and Instagram to remain connected with friends. A previous study conducted in South Africa found that text messaging and using social media were amongst the most frequent activities that adults using AAC engaged in on their mobile technology (Bornman, Bryen, Moolman, & Morris, 2016). Mobile technology with its portability, interconnectivity, and social acceptability can offer persons in need of AAC undeniable benefits (McNaughton & Light, 2013) and can support many valued adult roles (McNaughton & Bryen, 2007), including the initiation and maintenance of friendships.…”
Section: Role Of Technologymentioning
confidence: 99%